1980
DOI: 10.1007/bf00504535
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the renal vasodilator activity of dopamine by metoclopramide

Abstract: The interaction of metoclopramide with renal dopamine receptors has been characterized in anesthetized dogs surgically prepared with arterial blood pressure catheters and renal artery blood flowprobes. In normal dogs, i.v. dopamine (3 microgram/kg) produced consistent and selective decrements in renal vascular resistance (RVR) and increments in renal blood flow over a 220 min test period; mean arterial blood pressure and cardiac rate were minimally affected. Pretreatment with metoclopramide, 1 and 10 mg/kg i.v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The lack of antagonism of DA, receptors by doses of metoclopramide up to 145 /ug/kg in the present study is not inconsistent with reports that metoclopramide does antagonize DA, receptors when given in comparable doses directly into the renal artery 7 or when given intravenously, but in much higher doses (1000-10,000 /ng/kg). 26 The finding of a dosedependent antagonism of DA 2 versus DA, receptors by metoclopramide suggests that the affinity of this dopamine antagonist for the DA 2 receptor is greater than that for the DA, receptor. The results of the present study differ somewhat from those reported by Hamed et al 12 for PBDA.…”
Section: Emetic Potency Of N-alkyl Substituted Dopamine Analogs In Comentioning
confidence: 99%
“…The lack of antagonism of DA, receptors by doses of metoclopramide up to 145 /ug/kg in the present study is not inconsistent with reports that metoclopramide does antagonize DA, receptors when given in comparable doses directly into the renal artery 7 or when given intravenously, but in much higher doses (1000-10,000 /ng/kg). 26 The finding of a dosedependent antagonism of DA 2 versus DA, receptors by metoclopramide suggests that the affinity of this dopamine antagonist for the DA 2 receptor is greater than that for the DA, receptor. The results of the present study differ somewhat from those reported by Hamed et al 12 for PBDA.…”
Section: Emetic Potency Of N-alkyl Substituted Dopamine Analogs In Comentioning
confidence: 99%
“…Metoclopramide is a drug which mainly blocks the DA2 receptors [10] although at the dose employed in our study it can also block DAi receptors [22], During placebo administration, metoclopramide did not influence blood pressure and heart rate, slightly but not significantly decreased glomerular filtration rate, while renal plasma flow reduction was statistically signif icant; plasma noradrenaline and plasma renin activity were slightly but not significantly increased and plasma aldosterone significantly augmented. Some of these ef fects can be attributed to the blockade of DA2 receptors, as it is known that the activation of these receptors increases glomerular filtration rate [23] and inhibits aldosterone secretion [8,[24][25][26][27]; the significant decrease in renal plasma flow might be due either to activation of renal nerves (as DA2 receptor-mediated sympathetic in hibition [6,9,28]) or more probably to the blockade of renal DA!…”
Section: Discussionmentioning
confidence: 90%
“…In the present study we therefore reinvesti gated the effects of the predominant DA-2 receptor blocker MCP [40] in conscious rats. MCP had no effect on plasma ANP concen tration, urine flow or sodium excretion under control conditions, during gradual ECFV ex pansion or during stable ECFV expansion equal to a 10% increase in body weight.…”
Section: Discussionmentioning
confidence: 99%